2019
DOI: 10.1186/s40100-019-0125-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolving consumer trends for whey protein sports supplements: the Heckman ordered probit estimation

Abstract: Despite the fast-rising popularity of whey protein sports supplements over recent years, there has been little research to investigate the driving forces behind the consumer choices. Using a consumer dataset collected in Ireland, we applied the ordered Heckman two-stage method to examine the evolving consumer trend and to determine the key factors that affect consumers' choices. The study found that demographic variables, such as gender and income, do not significantly influence the decision on whether or not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…It proves that protein products are popular, and with the promotion of a healthy lifestyle, their demand will grow rapidly. The authors of [15] in their sociological studies found that demographic indicators (gender, income) did not significantly affect the choice of additives. Similar results were obtained by our team.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It proves that protein products are popular, and with the promotion of a healthy lifestyle, their demand will grow rapidly. The authors of [15] in their sociological studies found that demographic indicators (gender, income) did not significantly affect the choice of additives. Similar results were obtained by our team.…”
Section: Resultsmentioning
confidence: 97%
“…At the same time, despite the increase in demand for sports supplements (in particular, based on whey protein), studies on the consumer demand in this area have been insufficient [15].…”
Section: Methodsmentioning
confidence: 99%
“…In adolescents and adults, this is a known phenomenon. In the last decade, the idea of beauty shifted for women from a very slim to a more athletic, muscular body, which is reflected in a shift in the gender composition of protein consumers from male dominant to gender-neutral [ 27 ]. A Canadian study showed that comparison to idealized bodies on Instagram resulted in lowered confidence and increased body dissatisfaction in young women [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A problem frequently encountered in consumption research is that the amount of consumption cannot be observed for those who do not consume the product. Determining the amount of consumption according to the characteristics of only those who consume the product causes bias and inconsistency in the results obtained (Heckman 1979;Keogh et al, 2019). Therefore, the two-stage Heckman Model, which takes into account the problem of zero observation in the data analysis, developed by Heckman (1979) was used in the present study.…”
Section: Econometric Modelmentioning
confidence: 99%